Thiết kế và cài đặt hệ quản trị và xử lí dữ liệu - ảnh: DIMS - Ban, Đoàn Văn; Thắng, Giang Vũ; Tạo, Ngô Quốc (Journal of Computer Science and Cybernetics, 2016)
Based on relational model of data base we give design and implementation of data-image base management system, DIMS. This system has been devised to allow process, manage data and image base, is compatible with other management systems such as Dbase, FoxBase+, etc.